Mapping and Analysis of Geological Structures Based on GIS in Blega Subdistrict, Bangkalan Regency - Listyo Yudha Irawan; Azril Chairil; Zunan Faruq Ardiansyah; Rizal Sulaiman; Abdullah Alfarabi; Ravinesh Rohit Prasad; Nevy Farista Aristin (Universitas Lambung Mangkurat, 2025)
This research confirms that Blega Subdistrict, located in the southern part of Madura Island, is a structurally complex region within the Rembang Anticlinorium that requires detailed geological assessment due to its hazard potential and strategic land use. Through GIS-based integration of DEMNAS, Landsat 8, Sentinel-2A, geological maps, and field validation, the study identified asymmetrical folds trending S71°E and S75°E, with anticline limbs dipping at 30–40% on the southern flank and 25–35% on the northern flank, as well as four inactive faults oriented perpendicular to the fold axes. These structures, though no longer tectonically active, remain zones of weakness that affect slope morphology, groundwater infiltration, and mechanical stability. The results also show clear morphological contrasts, with the northern sector dominated by slopes exceeding 25% and locally reaching 55%, where slope instability, shallow landslides, and soil creep are most likely to occur, while the southeastern plains with slopes of 0–2% are prone to subsidence related to karst dissolution processes. This dual hazard scenario highlights that the geohazard potential in Blega is controlled not only by tectonic deformation but also by carbonate weathering and karstification, making it essential to consider geological structures and slope conditions in land use planning. The novelty of this work lies in providing a localized, quantitative characterization of structural patterns and hazard zones at the subdistrict scale, which has not been previously documented for Madura Island. By linking structural geology with slope analysis and land use, the study offers a practical foundation for risk-sensitive planning, disaster mitigation, and sustainable regional development in Bangkalan Regency.